A cloud-oriented integrity verification system for audio forensics. (January 2019) - Camacho, Steven; Ballesteros L, Dora M.; Renza, Diego
Abstract: Integrity analysis is an important task in the field of audio forensics. Its aim is to verify if an evidence (i.e. audio recording) has been manipulated or not. With the aim of providing a solution for the chain of custody, we propose a system that encompasses capture module, the hash value of the audio recording, cloud storage and integrity verification module. In order to validate the properties of the proposed hash function and its execution time, several tests were performed. According to the results, the user of our system can demonstrate/verify the integrity of the evidence in any moment after the recording process.